The Effects of Sintering Temperature on Structural, Electrical and Optical Properties of Sm0.5Ca0.5 MnO3 - Ravinthiran, Viknesvaran; Suhadir Shamsuddin, (Enhanced Knowledge in Sciences and Technology, 2024)
The article reports on the present status of knowledege in the field of matarial physics studies especially in ceramic industry. The artcle mainly focusing on solid state reaction method and sintering temperature effects on structural, electrical and optical properties of Sm0.5Ca0.5MnO3. There are plenty of studies on doping mechanisme using Sm0.5Ca0.5MnO3 but very less on sinteing temperature effects using divalent compound. Solid state reaction method used in the making of divalent compounds such as mixing, grinding, and pelleting. The determination of density was done with the application of Archimedes Principle and the calculation of porosity was made using the standard formula. The increase in bulk density and the decrease in porosity as sintering temperature rises. The resistivity increases as the sintering temperature increases. The samples were shown to have the same composition without any impurities through EDX analysis.